Синтез, кристаллическая структура и некоторые физико-химические свойства (СN3H6)2[(UO2)2(C7H3NO4)2(SO4)2]·H2O - V. I. Mishkevich; A. M. Fedoseev; M. N. Sokolova; N. A. Budantseva; E. E. Yakimova (Тонкие химические технологии)
A complex of composition (HGua)2[(UO2)2(di-Pic)2(SO4)2]·H2O (Gua = guanidine, di-Pic = anion of dipicolinic acid) was obtained. Single crystal X-ray diffraction showed that the structure of this compound is dimeric. Thermal decomposition, IR-spectrum and spectrum in visible range have been studied.